Os “usos políticos do passado” nas comemorações oficiais do biênio da colonização e imigração do Rio Grande do Sul (1974–1975) - Lima, Tatiane de (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation has as its main subject of investigation the official commemorations of the Biennium of the Colonization and Immigration that took place in Rio Grande do Sul in 1974 and 1975. Promoted by the State government, these commemorations were motivated by the upcoming 150th anniversary of the German Immigration and the 100th anniversary of the Italian Immigration. The initial goal of these celebrations was to honor the different immigrant groups who contributed to the ethnic composition of the State. However, during the commemorative process, the tributes were extended to include homage to native and Afro-descendent Brazilians, thus, changing the initial official discourse. Therefore, the main goal of this research is to make explicit how the government of Rio Grande do Sul used the immigrant past of the State during the commemorations of the Biennium of the Colonization and Immigration. To this end, the analysis of the commemorative process is constructed in three periods: 1) The organization of the celebrations. We analyzed the decree instituting the festivities, which determined actions to be taken during the commemorative process and the official ceremony opening the celebrations in the presence of the State government authorities. We also investigated the formation of the Tribute Commissions, composed by individuals authorized by the government, who were also responsible for the creation of the Commemorative Programs of their respective ethnic groups. Also, we mapped the municipalities participating in the festivities, and quantified and qualified the celebratory acts promoted in face of the dismembering of the Official Program. 2) The commemorations honoring the Luso-Brazilian pioneering, the 150th anniversary of German immigration, and the 100th anniversary of Italian immigration. By analyzing the reenactment of the arrival of German and Italian immigrants having as spectator President Ernesto Geisel, the promotion of events and creation of institutions incentivizing the studies of the immigrant history in the State, and the building of monuments, we confirmed the emphasis given to the celebration of these three groups. 3) The celebratory acts promoted in honor of native and Afro-descendent Brazilians. We analyzed the process extending the tributes to these ethnic groups, and its resulting change in the official discourse of these commemorations.
Keywords: Comemorações; Biênio da colonização e imigração; Usos políticos do passado; Celebrations; Biennium of the colonization and immigration; Political uses of the past; ACCNPQ::Ciências Humanas::História